Multiplexed fluid array screening of phage displayed anti-ricin single domain antibodies for rapid assessment of specificity. (December 2007) - Anderson, George P.; Matney, Russell; Liu, Jinny L.; Hayhurst, Andrew; Goldman, Ellen R.
Phage display is a well-known technique that facilitates the selection of peptides or proteins that bind to a desired target. Using this tool, binding elements contained in the natural immune repertoires of the source animal or from a synthetically generated collection may be selected. The unpaired variable domain of the llama's heavy-chain-only classes of immunoglobulins represents an ideal source of genetic material to create phage display libraries. Initial panning of a semi-synthetic llama library yielded only one binder to the toxin ricin. In an effort to increase the number of monoclonal phage binders selected, the Luminex xMAP technology (Luminex, Austin, TX, USA) was used in addition to the enzyme-linked immunosorbent assay (ELISA) to screen clonal populations of phage after three rounds of selection. The xMAP technology detected phage displayed single domain antibody (sdAb) bound to ricin immobilized on the surface of microspheres under equilibrium conditions. This enhanced capability led directly to the identification of additional single domain antibodies of interest. The selected sdAbs were expressed, purified, and then evaluated for their specificity as well as enhanced thermal stability in comparison to conventional immunoglobulin G (IgG). We determined equilibrium dissociation constants and demonstrated their use as effective capture molecules in sandwich immunoassays.